THE INFLUENCE OF MEDIA ON THE DEVELOPMENT OF ANCIENT PHILOSOPHICAL THOUGHT (Scientific journal of the Fergana State University, 2025)
This article examines the evolution of forms of media in Ancient Greece, their influence on the transmission of thought and the development of the ideas of great philosophers such as Thales, Anaximenes, Anaximander, Socrates, Plato, Aristotle. The article also examines the dialectic of the printed and written word and thinking.